Cross-language variation in the acceptability of vowelless nonwords - Zellou, Georgia; Afkir, Mohamed; Lahrouchi, Mohamed; Bensoukas, Karim (Frontiers in Communication, 2025)
This study examines the acceptability of voweled and vowelless nonwords produced by a native speaker of Tashlhiyt (a Moroccan Amazigh language) across listeners from five different language groups: L1 Tashlhiyt, L1 Tarifit, L1 Moroccan Arabic, L1 English, and L1 Mandarin. The languages vary in the complexity of allowable word types, though only Tashlhiyt allows lexically vowelless word forms. Hyper- and hypo-speech forms of the items were also compared in order to explore the effect of speaking style on listeners’ phonological knowledge. Results show gradient cross-language effects of nonword acceptability: compared to the native Tashlhiyt listeners, L1 Tarifit and L1 Moroccan Arabic listeners did not differ in their wordlike judgments. In contrast, L1 English showed lower and sonority-based wordlikeness preferences; L1 Mandarin listeners provided the lowest ratings of Tashlhiyt nonwords and were not sensitive to sonority variations. In contrast to the language-specific effect of word phonotactics, the role of clear speech in enhancing wordlikeness judgments was equivalent in effect size across language backgrounds.